2016
DOI: 10.1039/c5lc01517k
|View full text |Cite
|
Sign up to set email alerts
|

An integrated hybrid microfluidic device for oviposition-based chemical screening of adult Drosophila melanogaster

Abstract: Chemical screening using Drosophila melanogaster (the fruit fly) is vital in drug discovery, agricultural, and toxicological applications. Oviposition (egg laying) on chemically-doped agar plates is an important read-out metric used to quantitatively assess the biological fitness and behavioral responses of Drosophila. Current oviposition-based chemical screening studies are inaccurate, labor-intensive, time-consuming, and inflexible due to the manual chemical doping of agar. In this paper, we have developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Freely moving adult fruit flies inside the microfluidic channels were used to record their oviposition behavior where adult flies laid eggs on their preferential sites on a chemical-induced PDMS substrate (Fig. 4b) [7], and food-finding behavior [57]. Larvae of Danio rerio is also an important animal model that is used to study behavior responses.…”
Section: Behavioral Assaysmentioning
confidence: 99%
See 3 more Smart Citations
“…Freely moving adult fruit flies inside the microfluidic channels were used to record their oviposition behavior where adult flies laid eggs on their preferential sites on a chemical-induced PDMS substrate (Fig. 4b) [7], and food-finding behavior [57]. Larvae of Danio rerio is also an important animal model that is used to study behavior responses.…”
Section: Behavioral Assaysmentioning
confidence: 99%
“…Research performed by researchers showed how fruit fly larvae respond to heavy metals present in food [69]. A group of researchers studied oviposition (i.e., egg-laying) of the adult fruit fly [7,70]. Adult fruit fly has also been studied for observing how they and choose and approach the path for the food [7,57].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microfluidic technology has recently emerged as a powerful tool for neural and behavioral investigation of small model organisms such as C. elegans, [35][36][37][38][39][40][41][42] D. melanogaster, [43][44][45][46] and D. rerio. [47][48][49][50][51][52][53] Most recently, various microfluidic techniques have been introduced for precise manipulation, stimulation, and monitoring of zebrafish larvae's behavior.…”
mentioning
confidence: 99%